Korean Model for Post-acute Comprehensive rehabilitation (KOMPACT): The Study Protocol for a Pragmatic Multicenter Randomized Controlled Study on Early Supported Discharge - Chang, Won Kee; Kim, Won-Seok; Sohn, Min Kyun; Jee, Sungju; Shin, Yong-Il; Ko, Sung-Hwa; Ock, Minsu; Kim, Hyun Joo; Paik, Nam-Jong (Frontiers in Neurology, 2021)
Introduction: Early supported discharge (ESD) is a transitional care model aimed at facilitating post-acute stroke patients’ discharge to home. Previous studies have demonstrated that ESD provides equivalent patient and caregiver outcomes with superior cost-effectiveness compared to conventional rehabilitation (CR). This study intends to examine the feasibility of ESD in Korea. Methods and Analysis: This study is designed as a multicenter assessor-blinded, randomized controlled trial. Ninety post-acute stroke patients with mild to moderate disability (modified Rankin Scale 1-3) will be recruited from three university hospitals (30 patients per hospital) in Korea and allocated to either the ESD group or the CR group in a 1:1 ratio. Patients in the ESD group will receive individualized discharge planning and goal setting, a 4-week home-based rehabilitation program, and liaison service to community-based resources by a multidisciplinary team. Patients in the CR group will receive rehabilitation practices according to their current hospital policy. Outcomes: The primary outcome is the Korean version of the modified Barthel Index, and the primary endpoint was post-onset 3 months. Clinical outcomes, patient/caregiver reported outcomes, and socioeconomic outcomes will be measured at baseline, 1 month after discharge, 2 months after discharge, and 3 months after onset. Discussion: The efficacy and cost-effectiveness of ESD can vary according to the healthcare system and cultural perceptions. To establish ESD as an alternative transitional care model for post-acute stroke patients in Korea, its feasibility needs to be examined in the past. This study will add evidence on the applicability of ESD in Korea. Ethical Considerations: The study protocol was reviewed and approved by the Institutional Review Board of Seoul National University Bundang Hospital (IRB number B-2012/654-308). The study protocol was registered at ClinicalTrials.gov (Identifier NCT04720820). Disseminations will include submission to peer-reviewed journals and presentations at conferences.